Islamic Thought On The Prophet's Leadership And The Khulaf Al-Rashidin: The Real Sector And Public Finance And Its Relevance To The Modern Economy - Saeed Fayzul Hayat; Siradjuddin; Fatimah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the economic leadership of the Prophet Muhammad (peace be upon him) and the Caliphs (Rashidun Ulama) in managing the real sector and public financial system, and their relevance to the modern economy. Using qualitative-descriptive methods with a historical and analytical approach through literature review and content analysis techniques, this study examines classical and contemporary sources related to Islamic economics. The results indicate that the principles of justice, transparency, and social responsibility were the foundation of economic policy during that period, manifested through the ethical management of trade, agriculture, and industry, as well as the strengthening of fiscal institutions such as the Baitul Mal (the Islamic Public Treasury) and the Diwan (the Islamic Treasury). This system successfully rejected exploitative practices such as usury, gharar, and maysir (trading), while creating a stable economic structure oriented towards the welfare of the people. These findings demonstrate that classical Islamic economic values are relevant to addressing issues of social inequality, fiscal crises, and weak governance, and can serve as a foundation for developing ethical, inclusive, and sustainable modern economic policies.